A harmonics detection method based on triangle orthogonal principle for shunt active power filter. (September 2021) - Chen, Dongdong; Xiao, Long; Yan, Wenduan; Li, Yan; Guo, Yinbiao
Abstract: Harmonic current detection is a key algorithms for shunt active power filter controller, which generates reference currents to compensate the harmonics of grid current. This paper presents a new harmonics detection method based on the triangle orthogonal principle algorithm. Compared to the conventional harmonic current detection methods, the presented method has the advantages of simple structure, low calculation, and fast execution time. Using the phase signal detected by the phase-locked loop synchronized with the power grid signal, the method based on the triangle orthogonal principle can provide a simple method to detect the reference current. At the same time, because the method proposed in this paper has lower implementation complexity and less microcontroller resource consumption, low-cost microcontrollers can be used to implement the proposed method, which has practical engineering value. Finally, this paper analysis the proposed method in detailly and verifies its great performance through experimental results.